2009
DOI: 10.1002/anie.200802550
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of Hexahydropyrrolo[2,1‐b]oxazoles by a Rhodium‐Catalyzed Hydroformylation / Silica‐Promoted Deformylation Sequence

Abstract: Fleetingly formyl: A new rhodium-catalyzed hydroformylation reaction of N-allyl oxazolidines, carried out under a CO/H(2) atmosphere, followed by a diastereoselective deformylative cyclization affords hexahydropyrrolo[2,1-b]oxazoles in good yields. The reaction proceeds by a unique hydroformylation-deformylation sequence in which the formyl group virtually substitutes for the {CH(2)-O} fragment of the oxazolidine heterocycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…On the basis of previous studies and the results of our experiments [13,42,43,44,45,46,47,48,49,50,51,52,53], a possible reaction mechanism of the present reaction is proposed. Firstly, ( S )-BINOL reacted with Ti(O- i -Pr) 4 for two hours to give a complex A .…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…On the basis of previous studies and the results of our experiments [13,42,43,44,45,46,47,48,49,50,51,52,53], a possible reaction mechanism of the present reaction is proposed. Firstly, ( S )-BINOL reacted with Ti(O- i -Pr) 4 for two hours to give a complex A .…”
Section: Resultsmentioning
confidence: 51%
“…On the other hand, kinetic resolution, a powerful strategy in asymmetric synthesis, makes racemic substrates into optically-pure compounds [30,31,32,33,34,35,36,37,38,39,40,41]. Although many methods towards 1,3-oxazolidine skeletons have been developed, asymmetric synthesis of 1,3-oxazolidine with three components reaction involving kinetic resolution has not been well studied [42,43,44,45,46,47,48,49,50,51,52,53].…”
Section: Introductionmentioning
confidence: 99%
“…Although [ 13 C ]CO 2 could in principle also have been used for the same purpose using COware, Ba[ 13 C]CO 3 was chosen instead due to its lower price in the Sigma-Aldrich catalog. Six 13 C-labeled pharmaceutically relevant molecules (16,(94)(95)(96)(97)(98) could be prepared in good yields by using this methodology (Scheme 23).…”
Section: Carbonylative α-Arylations (C-c Bond Formation)mentioning
confidence: 99%
“…This is a useful tool for elucidating proposed mechanisms because of the high intensity of the 13 C-enriched carbon atom in 13 C-NMR spectroscopy. Vasylyev and Alper 94 have reported on the formation of hexahydropyrrolo [2,1-b] oxazoles through an unusual hydroformylation mechanism (113; Scheme 30A). The authors proposed that the olefin undergoes an initial hydroformylation, which was proven by using [ 13 C ]CO (Scheme 30A, left 13 C-NMR SCHEME 27 A-B, Using [ 13 C]CHCl 3 as a [ 13 C]CO-surrogate SCHEME 28 A-C, Decarbonylation of [ 13 C]formic acid via a mixed anhydride strategy spectrum) followed by a silica-gel mediated cyclization eliminating unlabeled formaldehyde.…”
Section: [ 13 C]co For Mechanistic Studiesmentioning
confidence: 99%
“…We found that cyclic N,O-acetals can be prepared diastereoselectively by a hydroformylation-SiO 2 -induced deformylation reaction sequence starting from the easily accessible chiral N-(allyl)oxazolidines 19. 18 The method made it possible to synthesize the five-membered 5-unsubstituted oxazabicycloalkane ring systems, which were not previously accessible by hydroformylation-acetalization of 2-(alkenylamino)ethanols and prepared previously only by a stoichiometric oxidative cyclization of 2-pyrrolidino-1-ethanol derivatives. 19 An example of the developed hydroformylation-SiO 2 -induced deformylation reaction is shown in Table 10, where hydroformylation of (4R)-3-allyl-4-phenyloxazolidine (19a), followed by a silica-induced diastereoselective deformylative cyclization affords (3R,7aS)-3-phenylhexahydropyrrolo[2,1-b]oxazole (20a) in 87% yield.…”
Section: Figure 3 Generation G1 Rhodium Dendrimer-grafted Resin Complexmentioning
confidence: 99%